Estimation of counterfactual schooling outcomes using inverse propensity score reweighting - Abrigo, Michael Ralph M. (Quezon City University of the Philippines, 2012)
Abstract (Impacts of international labor migration and remittances to the economy, both at the household and aggregate levels, have well been documented in the literature. At the micro-level analysis, however, focus has often been confined on the binary treatment assignment of remittance-receipt and/or migrant-membership among households. This may mas finer but important impacts which nay be revealed with a more disaggregated anaylsis. This study contributes to the migration and development literature by estimating the impact of migration of either parent on schooling participation and performance of children left behind. To cope with the multi-level non-binary treatment assignments in the study, re-weighting based on the propensity score in used to provide valid counterfactual distribution of the outcomes. Children of migrant parents perform better in school participation and performance relative to children of non-migrant parents. Furthermore, while school attendance is variant of who among the parents migrate, children of migrant father perform better in school. This highlights the nurturing role of mothers in child-rearing, especially with regards education of children).
Thesis ( M.S.) --University of the Philippines.